IVF under COVID-19: treatment outcomes of fresh ART cycles. Issue 5 (25th February 2022) - Youngster, Michal; Avraham, Sarit; Yaakov, Odelia; Landau Rabbi, Moran; Gat, Itai; Yerushalmi, Gil; Sverdlove, Rachael; Baum, Micha; Maman, Ettie; Hourvitz, Ariel; Kedem, Alon
Abstract: STUDY QUESTION: Does prior severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection in women undergoing fertility treatments affect the outcomes of fresh ART cycles? SUMMARY ANSWER: SARS-CoV-2 infection does not affect fresh ART treatment outcomes, except for a possible long-term negative effect on oocyte yield (>180 days postinfection). WHAT IS KNOWN ALREADY: A single previous study suggested no evidence that a history of asymptomatic or mild SARS-CoV-2 infection in females caused impairment of fresh ART treatment outcomes. STUDY DESIGN, SIZE, DURATION: Retrospective cohort study, including all SARS-CoV-2 infected women who underwent fresh ART cycles within a year from infection (the first cycle postinfection), between October 2020 and June 2021, matched to non-diagnosed controls. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients from two large IVF units in Israel who were infected with SARS-CoV-2 and later underwent fresh ART cycles were matched by age to non-diagnosed, non-vaccinated controls. Demographics, cycle characteristics and cycle outcomes, including oocyte yield, maturation rate, fertilization rate, number of frozen embryos per cycle and clinical pregnancy rates, were compared between groups. MAIN RESULTS AND THE ROLE OF CHANCE: One hundred and twenty-one infected patients and 121 controls who underwent fresh ART cycles were included. Oocyte yield (12.50 versus 11.29; P = 0.169) and mature oocyte rate (78% versus 82%; P = 0.144) in all fresh cycles were similar between groups, as were fertilization rates, number of frozen embryos per cycle and clinical pregnancy rates (43% versus 40%; P = 0.737) in fresh cycles with an embryo transfer. In a logistic regression model, SARS-CoV-2 infection more than 180 days prior to retrieval had a negative effect on oocyte yield ( P = 0.018, Slope = −4.08, 95% CI −7.41 to −0.75), although the sample size was small. LIMITATIONS, REASONS FOR CAUTION: A retrospective study with data that was not uniformly generated under a study protocol, no antibody testing for the control group. WIDER IMPLICATIONS OF THE FINDINGS: The study findings suggest that SARS-CoV-2 infection does not affect treatment outcomes, including oocyte yield, fertilization and maturation rate, number of good quality embryos and clinical pregnancy rates, in fresh ART cycles, except for a possible long-term negative effect on oocyte yield when retrieval occurs >180 days post-SARS-CoV-2 infection. Further studies are warranted to support these findings. STUDY FUNDING/COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: 0010-21-HMC, 0094-21-ASF.